Pengendali Wiper dan Washer Otomatis Menggunakan Sensor Hujan dan Sensor Debu Berbasis Arduino - Reni Rahmadewi; Wilma Nurrul Adzillah; Endah Purwanti; Vita Efelina; Raka Wahyu Utama (Sekolah Tinggi Teknologi Wastukancana, 2020)
Safety in driving is an important thing that must be considered to avoid traffic accidents. One of the factors causing the accident is the weather with a percentage reaching 13%, the driver will not focus on driving the car. Wiper control technology and automatic washer are applied to facilitate humans in driving. This system reads the intensity of rain and dust with a sensor then automatically the data is processed with a microcontroller. The output used in this system uses a stepper motor and Washer pump motor. Uses Arduino Uno and Fuzzy logic to make it easy as an automatic control system. The experimental results obtained are the speed of movement of the Wiper adjusts to the amount of water and dust input intensity received by the sensor. The success value of the Matlab output with the manual count output value is 98.26%, between the value of the manual count output with the actual output value of 96.83% and between the Matlab output value with the actual LCD output value of 96.95%